Léxico e livro didático: estratégias para o desenvolvimento da leitura - Ana Flavia Torquetti Domingues Cruz (2015)
The advances made in recent decades with regard to mother tongue teaching attach to the text, in reading or in writing, an important role in the classroom, which deconstructs the school practices that overestimate the teaching of grammar rules. In line with the proposals thatcombine the used language to the pedagogical demands, lexicons scholars have sought alternatives to a more assertive treatment of this aspect in this context, since it has been neglected by teachers and authors of teaching materials, although the word constitutes, inessence, any verbal text. Faced with few changes perceived in the treatment of the lexicon in teaching materials, which has negative repercussions, for example, in reading skills to be developed by students-readers, this study in Applied Linguistics aims to list the strategies that combine the lexicon teaching and reading from a text view. Another purpose of this work is to understand how the teaching collection intended for elementary school entitled Projeto Teláris Português (Telaris Project Portuguese) combines the above aspects, which led to the proposal to reformulate some of the exercises of such textbooks. Relying, as well, in Linguisticsand researches made by Orlandi (1999), Travaglia (2002), Antunes (2003), Dell'Isola (2005), Ferraz (2006), Elias and Koch (2012) and Kock (2014), this paper intends to contribute to the development of language skills of Brazilian students.